Etika Komunikasi dalam Bermedia Sosial di Kalangan Siswa Sekolah Menengah Atas (SMA) di Kabupaten Kudus - Karina Eka Listiya Pratiwi Pratiwi; Puji Rianto Rianto (Program Studi Ilmu Komunikasi UII, 2023)
The presence of social media has had an impact on changes in human behavior and attitudes toward communicating. Through social media, information can be spread widely, freely, and quickly. Users have greater freedom in selecting, producing, and sharing messages on social media. This freedom imposes ethical responsibilities on users, including young people. This study explains the ethics of social media among high school (SMA) students in Kudus Regency. This study used a mixed sequential explanatory method. The method involves both quantitative and qualitative. The data in this study were obtained through surveys and focus group discussions (FGD). The survey was carried out by asking students' attitudes toward the ethical statements given. The research results show that the average respondent has a high ethical attitude. For the eight ethical dimensions that were asked when using social media, the average percentage of agreeing and strongly agreeing was large. Only a few stated that they disagreed or strongly disagreed. The FGD results confirmed the survey findings.